FACILITY LEVEL FACTORS IN VA COMMUNITY LIVING CENTERS AND RESIDENTS' CHALLENGING BEHAVIORS. (11th November 2018) - Mach, J; Jedele, J; McCarthy, J
Abstract: Challenging behaviors among residents pose important concerns for quality of life and quality of care in nursing home settings, including Veterans Affairs (VA) Community Living Centers (CLCs). It is anticipated that the availability of mental health (MH) service professionals may help to address challenging behaviors among CLC residents. This study examined associations between CLC characteristics and average scores for behavior challenges per residents' Minimum Data Set (MDS) assessments among 101 VA CLCs that completed a 2010 national survey. Using Poisson regression, we examined associations between 12 site reports (e.g., mental health availability, specialized training for mental health and dementia, and availability and staffing for dementia and behavioral health units) and average scores for resident behaviors (Physical aggression [PA]; Verbal aggression [VbA]; Socially inappropriate behavior [SI]; Resisting care [RC], and Wandering). Analyses adjusted for 5 facility and 8 patient factors. Factors associated with statistically significantly higher scores (p<0.05) included: 1) specialized training for dementia (significant coefficients: VBA=0.48, SI=0.40, Wandering=0.42); 2) MH training (VBA=0.89, SI=0.76, PA=1.43, Wandering=1.00); 3) 24-hour coverage by RN in specialized MH area (Wandering=0.97); 4) nurse training for 1/3-2/3 of nurses (SI=0.31, Wandering=0.52). Significantly lower average scores were documented for 1) MH availability within the CLC (Wandering=-0.52); 2) MH availability outside the CLC (Wandering=-0.75); and 3) RN 24-hour coverage in dementia area (PA=-0.54). CLC site reports, including MH availability and dementia training and staffing, are associated with average scores for resident challenging behaviors. Findings may inform ongoing work to enhance services in VA CLCs.